Health impact of shift work and night duty on part-time studying nurses - Manyeneng, Lorato G. (Orapuh Journal, 2025)
Introduction In the demanding field of nursing, professionals often find themselves navigating the challenges of shift work and night duty, primarily due to a persistent shortage of nursing staff. This situation compels nurses to take on overtime and unconventional hours to meet the healthcare needs of their communities. Some nurses also pursue further education part-time, frequently opting for night shifts to accommodate their daytime classes. However, the toll of working irregular hours can lead to significant health consequences, including burnout and an increased risk of chronic health conditions.PurposeThe study aimed to investigate the health impacts among nursing students working shifts and night duty while enrolled part-time at a higher learning institution in Gauteng, South Africa.MethodsA descriptive quantitative methodology was employed, utilizing convenience sampling to gather data from 175 part-time nursing students at a designated higher education institution. Data collection was conducted over a three-month period using a structured questionnaire comprising both open-ended and closed-ended questions. The questionnaire was designed to assess variables related to the study objectives. Descriptive statistical approaches were employed, and data were analysed using SPSS version 26.ResultsThe majority of nursing students were females (81%, n=142), while males constituted 19% (n=33). Among the 175 respondents, the findings revealed that 43% (n=64) experienced insomnia, 40% (n=59) reported fatigue, 7% (n=11) indicated difficulties with night driving, 6% (n=9) reported stress, and 3% (n=5) noted that their social lives were affected. Additionally, 15% (n=27) of the respondents were not exposed to shift work and night duty.ConclusionThe study highlights the significant challenges faced by part-time nursing students who juggle shift work and academic responsibilities, particularly in relation to fatigue and insomnia. It underscores the need for enhanced support from higher learning institutions and employers to mitigate these health risks.